Knowledge of Hand Hygiene practices among trainees of a medical college in South Karnataka - Meghana B.M.; Sathish J.V.; Vijaykumar Mane; Trupti B. Naik (International Journal of Health and Clinical Research, 2022)
Background: Hand hygiene is a simple measure that plays an important role in the reduction of the incidence of healthcare-associated infections. Compliance with adequate hand hygiene practices among the healthcare workers is only 40%. Objective: To estimate the level of Knowledge about Hand hygiene among the trainees of medicine at a tertiary care teaching hospital. Materials and methods: The present study was a cross-sectional study done for a duration of 3 months from September 2021 to November 2021 among 140 interns at a Government Medical College, Chamarajanagar. Data were collected by using the "WHO hand hygiene questionnaire for health care workers" and analyzed using Microsoft office excel 2010. Results: Only 23 (16.4%) of interns had a strong knowledge of hand hygiene while the majority had moderate understanding 97 (69.2%). Conclusion: Awareness regarding Hand hygiene practices needs to be improved through regular sensitization workshops and onsite practical guidance.